An ergonomic study on the 'morningness' and 'eveningness' of call center agents and its effect on cognitive performance - Gutierrez, Alma Maria Jennifer A. (Animo Repository, 2017)
The increasing adaptation of shiftwork in the Philippines and its reported adverse effects had encouraged research studies among Filipino workers. This study aims to identify the circadian clock behavior of the shiftworker and its relationship together with the shift schedule against the level of performance. The subjects used in this study were call center agents. Subjects were initially asked to answer a compilation of survey from the Standard Shift work Index (SSI) and Swedish Occupational Fatigue Inventory (SOFI). During the experiment proper, three laptops with head microphones were used where each laptop contained the software and programs in measuring the speech ability, reaction time and memory of participants. Majority of the respondents belong to the morning type and only one belonged to the intermediate type. The General Health Score (SSI) of the agents was generally poor in the aspect of their psychological health. The Swedish Occupational Fatigue Inventory (SOFI) scores showed that the respondents did not experience excessive fatigue. Based on the two-way ANOVA, it was found that the three speech ability measures and reaction time were significant in terms of the performance deterioration at each schedule in relation to the body clock of the individual. © 2017 IJTech.